2013
DOI: 10.1371/journal.pone.0085857
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Vitreous Levels of Matrix Metalloproteinases and Vascular Endothelial Growth Factor in Proliferative Diabetic Retinopathy

Abstract: To investigate which matrix metalloproteinases (MMPs) are more likely to be involved in the angiogenic process in proliferative diabetic retinopathy (PDR), we measured the levels of MMPs in the vitreous fluid from patients with PDR and controls and correlated these levels with the levels of vascular endothelial growth factor (VEGF). Vitreous samples from 32 PDR and 24 nondiabetic patients were studied by mosaic multiplex MMPs enzyme-linked immunosorbent assay (ELISA), single ELISA, Western blot and zymography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 33 publications
4
79
0
2
Order By: Relevance
“…Incubation of retinal endothelial cells with PJ34 or PARP-1 siRNA, or administration of PJ34 in vivo significantly inhibited the binding of NF- k B and AP-1 at the MMP-9 promoter, suggesting an important role of PARP-1 in promoting transcription initiation complex formation at the MMP-9 promoter. This is in agreement with a previous observation where PARP-1 deletion is shown to contribute to a defective activation of transcription factors critical in tumor development [46, 47]…”
Section: Discussionsupporting
confidence: 94%
“…Incubation of retinal endothelial cells with PJ34 or PARP-1 siRNA, or administration of PJ34 in vivo significantly inhibited the binding of NF- k B and AP-1 at the MMP-9 promoter, suggesting an important role of PARP-1 in promoting transcription initiation complex formation at the MMP-9 promoter. This is in agreement with a previous observation where PARP-1 deletion is shown to contribute to a defective activation of transcription factors critical in tumor development [46, 47]…”
Section: Discussionsupporting
confidence: 94%
“…Abu et al found significant increases in vitreous zymography levels of MMP-9 in PDR patients (392.3 ± 253.6 scanning units) compared to non-diabetic control patients (168.2 ± 65.0 scanning units). However, the levels of vitreous MMP-2 in PDR patients (540.9 ± 185.6 scanning units) did not differ significantly from non-diabetic control patients (505.4 ± 216.1 scanning units) [60]. Inhibitors of MMPs have been used to treat several diseases, however, there have been no studies using these inhibitors to treat DR patients [59].…”
Section: Matrix Metalloproteinasesmentioning
confidence: 91%
“…Several studies suggest that MMPs are responsible for many diabetic complications, including cardiomyopathy, nephropathy, and retinopathy. MMPs are suspected to facilitate apoptosis of retinal capillary cells during early stages leading to disruption of blood-retinal barrier integrity [58][59][60]. Kowluru et al found an increase in MMP-9 and a decrease in TIMP-1 in the retina of DR patients [58].…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%
“…175 MMP-2 is constitutively expressed in normal vitreous and probably regulates collagen turnover and the degradation of gelatin (denatured collagen) and a number of cytokines, including TGFβ. 176,177 Multiple hormones, cytokines and growth factors regulate MMP expression and, in vitreal pathology such as diabetic retinopathy and retinal vein occlusion, increased expression is associated with VEGF expression. 176,178 MMP-12 is important for macrophage migration in murine retina and vitreous but has not been detected in human vitreous.…”
Section: Timp and Mmpmentioning
confidence: 99%